Spatial-Temporal Land Use Change in Depati Amir Airport Based on Google Earth Imagery - Putri, Niken Anissa; Wibowo, Adi (Journal of Community Based Environmental Engineering and Management, 2023)
The new Depati Amir Airport was built in 2013, which can destroy the natural vegetation due to the airport’s development and extensive buildings. The research aims to identify and analyze the spatial‐temporal land‐use change characteristics in the new Depati Amir Airport. The land use change detections are in the new Depati Amir Airport by spatial-temporal analysis with three land use maps (2004, 2014, and 2022) on Google Earth Imagery. Google Earth Imagery is analyzed with QGIS to assess spatiotemporal land use changes in the new Depati Amir Airport between 2004, 2014, and 2022. Depati Amir Airport, as the new airport in Bangka Tengah Regency, has influenced land use change in Bangka Tengah Regency. The new Depati Amir Airport land types are buildings, including roads, natural vegetation, tin mining, and open space. The three new Depati Amir Airport Imagery in 2004, 2014, and 2022 on Google Earth Data can examine land use changes that depict red, orange, purple, and green rectangles. The natural vegetation and tin mining decreased due to the development of a new airport, such as roads, open spaces, and extensive buildings with a significant transformation. Hence, understanding the land use changes for local governments, regional planners, and scientific communities require close attention to spatial to reach crucial knowledge.